The Influence of Trichoderma harzianum on the Root-knot Fusarium Wilt Complex in Cotton - Yang, Henry (Society of Nematologists, 1976)
Wilt-susceptible cultivar 'Rowden' cotton was inoculated wilh Meloidogyne incognita (N), Trichoderma harzianum (T), and Fusarium oxysporum f. sp. vasinfectum (F) alone and in all combinations in various time sequences. Plants inoculated with F alone or in combination with T did not develop wilt, Simultaneous inoculation of 7-day-old seedlings with all three organisms (NTF) produced earliest wilt. However, plants receiving nematodes at 7 days and Fusarium and Trichoderma at 2 or 4 weeks later (N-T-F, N-TF) developed the greatest wilt between 49-84 days after initial nematode inoculation. During the same period, Fusarium added 4 weeks after initial nematode inoculation (N-F) and Fusarium added 4 weeks after initial simultaneous inoculation of nematode and Trichoderma (NT-F) produced the least wilt. The addition of Fusarium inhibited nematode reproduction. Simultaneous inoculation with nematodes and Trichoderma (NT-) resulted in the greatest root gall development, whereas nematodes alone produced the greatest number of larvae. In comparison with noninoculated controls (CK), treatments involving all three organisms inhibited plant growth, plants inoculated with the nematode alone (N-) or with nematodes and Trichoderma (NT-) simultaneously had greatest root weight. Any treatment involving the nematode resulted in fewer bolls per plant and greater necrosis on roots than the noninoculated checks.